2006
DOI: 10.1002/nme.1848
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐linearity algorithm for wall slip in two‐dimensional gap flow

Abstract: SUMMARYWall slip has been observed in a micro/nanometer gap during the past few years. It is difficult to make a mathematical analysis for the hydrodynamics of the fluid flowing in a gap with wall slip because the fluid velocity at the liquid-solid interface is not known a priori. This difficulty is met especially in a two-dimensional slip flow due to the non-linearity of the slip control equation. In the present paper we developed a multi-linearity method to approach the non-linear control equation of the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…As shown in Fig. 7, all the film thicknesses were located in the region bounded by the two theoretical curves, indicating that critical shear stress decreases (i.e., a reduction in adhesion strength) with the drop of film thickness [28,29]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 69%
“…As shown in Fig. 7, all the film thicknesses were located in the region bounded by the two theoretical curves, indicating that critical shear stress decreases (i.e., a reduction in adhesion strength) with the drop of film thickness [28,29]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 69%
“…Afterwards Li and co-workers coupled other effects such as the (i) flow rheology [17] and (ii) surface roughness [18] to anisotropic boundary slip to more accurately evaluate the performance of journal bearings. Ma and co-workers [19,20] have proposed an extension of the Tresca slip-model for the analysis of twodimensional journal bearings. They assumed a polygonal approximation of the theoretical slip-limit circle and identified suitable complementarity variables to solve the slip problem adopting quadratic programming techniques.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…While our mass-conserving cavitation algorithm has already been demonstrated to be able to simulate these cases, some modifications need to be implemented to predict the slippage in two dimensions, see Ref. 20 A similar procedure can be followed for the y-direction. By substituting z = h in Equation A.4, the velocity of the fluid layer in contact with the upper slipping surface in the x-direction, U s , can be obtained:…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Moreover, they analyzed the load-carrying capacity, friction and other lubrication characteristics of infinite-width bearings. Ma et al (2007a, 2007b) extended the quadratic programming algorithm to the solution of two-dimensional surface slip and found that the inclusion of a slip surface could distinctly improve the hydrodynamic load-carrying capacity.…”
Section: Introductionmentioning
confidence: 99%